A Multifrequency Method for Determining Cochlear Efferent Activity - Luebke, Anne E. (Springer-Verlag, 2001)

(untitled)
A test based on measures of distortion-product otoacoustic emissions (DPOAEs) was developed in lightly anesthetized guinea pigs and alert rabbits to assess the effective activation or functional "strength" of the cochlear efferent system. The multifrequency method described here used the DP-gram frequency function to evaluate the fast component of the olivocochlear adaptive effect on DPOAE levels over a 2-octave frequency range. An estimate of any concurrent muscle activation was also determined over the identical frequency range by monitoring the levels of the eliciting f(1) primary tone throughout its duration. The acoustic reflex, as measured by this f(1) level constancy test, did not appear to contribute to the average efferent strength of sedated guinea pigs, but the acoustic reflex did contribute to the average "efferent" strength of awake rabbits. Hence, the average efferent effect in alert rabbits is contaminated by the acoustic reflex, which confounds its interpretation.